Study of sexual dimorphism of Malaysian crania: an important step in identification of the skeletal remains (vol 50, pg 86, 2017) - Ibrahim, A; Alias, A; Nor, FM; Swarhib, M; Abu Bakar, SN; Das, S; Abdullah, N; Noor, MHM (Medrang, 2024)
Indexed by WOS